DOWODY Z DOKUMENTÓW POŚWIADCZONYCH ZA ZGODNOŚĆ Z ORYGINAŁEM PRZEZ PROFESJONALNEGO PEŁNOMOCNIKA W POSTĘPOWANIU W SPRAWIE O WPIS W KRAJOWYM REJESTRZE SĄDOWYM - Stanik, Mariusz (Zeszyty Prawnicze, 2016)
DOCUMENTARY EVIDENCE CERTIFIED AS TRUE BY A PROFESSIONAL PROXY IN PROCEEDINGS FOR AN ENTRY IN THE NATIONAL COURT REGISTER Summary The article concerns the acceptable form of documentary evidence in proceedings for an entry in the Polish National Court Register, in particular whether as of 1 January 2010 it is permissible to attach documents certified as true copies by the proxy appearing in the case, that is an attorney, legal representative, or attorney of the Polish State Treasury Office, to applications for entry in the Register. The analysis of this issue examines the provisions of Art. 129 § 3 and Art. 6944 § 1 of the Polish Civil Procedure Code, including an analysis of the relation between these provisions. In conclusion the author observes that despite the fact that there is a lex generalis ‒ lex specialis relations between Art. 129 § 3 and Art. 6944 § 1 of the Code, the principle of lex specialis derogat legi generali does not apply. Consequently, in the proceedings for entry in the Register there are no legal obstacles for the submission of documents on the basis of which entries are to be made in the Register, in the form of copies or transcripts certified as a true copy by the acting proxy (attorney, legal representative, or attorney of the State Treasury Office) of the party to such proceedings.